GAMIFIED ENGLISH LEARNING: EVALUATING DUOLINGO MOBILE APPS IMPACT ON DET PERFORMANCE AMONG INDONESIAN COLLEGE STUDENTS - Istighfaroh, Faridatul (Jurnal Pendidikan Bahasa Inggris Proficiency, 2025)
This study explores the effectiveness of Duolingo, a well-known English mobile application, in enhancing university students’ scores on the Duolingo English Test (DET). The DET itself has transformed to be an official English assessment like TOEFL or IELTS and has been recognized by institutions abroad. The research employed a quasi-experimental design which involved 110 EFL students in an Indonesian university who were asked to use Duolingo consistently for 7 weeks. Pre-test and post-test of DET scores were gathered to measure the impact of regular Duolingo use. The findings revealed a sig (2-tailed) value of 0.001 (0.001 < 0.05) which shows there is an improvement in the university students’ DET scores in the 7th week after intervention, especially on vocabulary, reading and listening comprehension. The results suggest that incorporating mobile-assisted language learning tools like Duolingo can be an effective strategy to enhance students’ English proficiency and test performance. This study contributes to the rising evidence supporting technology involvement in English language learning, especially in preparation for standardized English tests like DET.